Exploring the Analgesic Effect of Acupuncture on Knee Osteoarthritis Based on MLT/cAMP/PKA/CREB Signaling Pathway - Zhang C; Yu M; Zhang L; Zhou X; Han J; Fu B; Xue H; Zhang C (Journal of Inflammation Research)
Chao Zhang,1,2,* Man Yu,3,* Longyao Zhang,1,2 Xin Zhou,1,2 Jinchang Han,1,2 Bifeng Fu,1,2 Hongfei Xue,1,2 Chao Zhang1,2 1Orthopedics Department, The First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, 300380, People’s Republic of China; 2National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, 300380, People’s Republic of China; 3Department of Nephrology and Rheumatology, Second Hospital Affiliated to Tianjin University of Traditional Chinese Medicine, Tianjin, 300250, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongfei Xue; Chao Zhang, The First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, 300380, People’s Republic of China, Email 2538287036@qq.com; zhangchao2004.love@163.comBackground: Acupuncture is an effective treatment for knee osteoarthritis (KOA), reducing pain and improving function. While melatonin (MLT) has notable pain relief benefits, the analgesic mechanism of acupuncture in KOA and its relationship with melatonin are still unknown. This study aims to explore this mechanism.Methods: In this work, the KOA rabbit model was constructed using the traditional Hulth method, and the therapeutic effect was assessed by the Lequesne MG score and Pain assessment by hot plate test. The pathological alterations of cartilage tissue were observed using hematoxylin and eosin (H&E) staining, Safranin O-fast green and MASSON staining to observe the pathological changes in cartilage tissue, and the efficacy was evaluated according to the principles of Mankin score and Osteoarthritis Research Society International (OARSI) score. Meanwhile, MLT in serum, cyclic adenosine monophosphate (cAMP) in cartilage, and matrix metalloproteinase-3 (MMP-3) in joint fluid were detected by enzyme-linked immunosorbent assay. In addition, the expression of aromatic L-amino acid N-acetyltransferase (AANAT), melatonin receptor 1 (MT1) and 2 (MT2) mRNAs in cartilage was determined by real-time quantitative reverse transcription-polymerase chain reaction, and the levels of proteins related to PKA/CREB signaling pathway were detected by Western blotting.Results: Based on the results of Lequesne MG score and Pain assessment by hot plate test experimental data, the treatment group presented significant improvements in knee pain and overall function relative to OA (Osteoarthritis) group. Besides, according to results of histologic staining, Mankin and OARSI scores, articular cartilage degeneration of treatment group remarkably improved. In addition, acupuncture significantly reduced the expression of the inflammatory factor MMP-3 in knee joint fluid and significantly increased the levels of MLT, AANAT, MT1, MT2, cAMP, PKA and CREB.Conclusion: By regulating sympathetic excitability, acupuncture may activate the MLT/cAMP/PKA/CREB signaling pathway, decrease inflammatory factor expression and slow down degradation of articular cartilage, resulting in the relief of knee pain.Keywords: acupuncture, knee osteoarthritis, MLT/cAMP/PKA/CREB pathway, melatonin